2021
DOI: 10.1021/acsestwater.1c00096
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Toxicity of Road Salt Alternatives to Freshwater Mussels; Examining the Potential Risk of Eco-Friendly De-icing Products to Sensitive Aquatic Species

Abstract: The negative impact of road salt on freshwater ecosystems has led to an interest in “eco-friendly” de-icing products. Biota, including freshwater mussels that have heightened salt sensitivity, would be expected to benefit from a transition to alternative de-icing products. However, it was unknown whether the alternatives themselves pose a risk. The toxicity of three road salt alternatives including a salt brine, a beet juice, and a brine–beet juice product were examined. Lampsilis fasciola glochidia (larvae) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…After release from the maternal brood, glochidia experienced both a brief direct exposure to contaminants during host fish infestation and potential indirect exposure while encysted on host fish. Few studies address the importance of host fish contaminant exposure relative to glochidia exposure in determining transformation rates, but available evidence indicates glochidia exposure as a more important factor (Jacobson et al, 1997 , Hazelton et al, 2012 , Beggel and Geist, 2015 , Gillis et al, 2021 ). Maternal unionids, glochidia, and host fish were from the same exposure duration treatments, and thus we cannot determine if juvenile transformation was influenced by host fish exposure, direct contact of glochidia with CECs during infestation, or previously discussed glochidia exposure in brood.…”
Section: Discussionmentioning
confidence: 99%
“…After release from the maternal brood, glochidia experienced both a brief direct exposure to contaminants during host fish infestation and potential indirect exposure while encysted on host fish. Few studies address the importance of host fish contaminant exposure relative to glochidia exposure in determining transformation rates, but available evidence indicates glochidia exposure as a more important factor (Jacobson et al, 1997 , Hazelton et al, 2012 , Beggel and Geist, 2015 , Gillis et al, 2021 ). Maternal unionids, glochidia, and host fish were from the same exposure duration treatments, and thus we cannot determine if juvenile transformation was influenced by host fish exposure, direct contact of glochidia with CECs during infestation, or previously discussed glochidia exposure in brood.…”
Section: Discussionmentioning
confidence: 99%
“…Working with the freshwater mussel Anodonta imbecilis, Keller and Zam (1991) found that two-metal mixtures including Cu, Ni, and/or Zn were generally more toxic, as determined by 24-and 48 h median lethal concentrations (LC50s), than single-metal exposures; but two-metal mixtures including Cd tended to be less toxic by that measure. Gillis et al (2021) observed greater sensitivity of freshwater mussel Lampsilis fasciola glochidia (larvae) to chloride when a complex mixture of metals was included in the exposure. Both Appalachian coal-mine spoil leachates and mining-influenced sections of the Clinch and Powell Rivers are known to be elevated in multiple constituents, including Al, As, Cd, Mn, and/or Se as well as the three metals studied here (Zipper et al, 2016;Clark et al, 2018;VDEQ/TDEC, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…Noticeably, Rogers et al (2023) recently found a significantly greater abundance of tissue abnormalities in digestive glands and kidneys of subadult rainbow mussel ( Villosa iris ) at exposure concentrations of as low as 4.2 mg K/L relative to the control after a 61‐day KCl exposure in a pond water (hardness ~210 mg/L as CaCO 3 ), indicating that effect concentrations on mussel organ tissues could be below the chronic effect concentrations based on mussel survival and growth. Glochidia and juvenile mussels are also highly sensitive to acute KCl exposures (Gillis et al, 2021; Salerno et al, 2019; Wang, Ivey, Dorman, et al, 2018). Potassium is often elevated in industrial and municipal wastewater treatment plant effluents and in discharges from oil and gas production operations (Kunz et al, 2021; Liden et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Potassium is often elevated in industrial and municipal wastewater treatment plant effluents and in discharges from oil and gas production operations (Kunz et al, 2021; Liden et al, 2018). The importance of developing water quality guidelines for protecting mussels and other sensitive organisms has been well addressed in several publications (Gillis et al, 2021; Kunz et al, 2021; Wang et al, 2017; Wang, Ivey, Dorman, et al, 2018).…”
Section: Resultsmentioning
confidence: 99%